SAN LUIS POTOSIECTROPHOTOMETRY OF THE ORION NEBULA II THE ABUNDANCE OF ELEMENTS - MENDEZ, ME (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1965)
Using a recent spectrophotometric study of the Orion Nebula, the chemical composition of this object is derived. The electron temperature is also given. The abundance by mass is X = 0.713; Y = 0.26 +/- 0.02; Z = 0.027 +/- 0.004, which is very close to the
BOL OBS TONAN TACUB
Keywords: SPECTROPHOTOMETRY, ORION NEBULA, II, ABUNDANCE, ELEMENTS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS